Effect of Cerium Ion on Microstructure and Dielectric Properties of Ni-Zn Ferrites Prepared by Solid State Reaction Method - Hitler, Amna M.; Saadon, Abbas K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In this work, the Nickel and zinc Ferrite Ni0.5Zn0.5 Fe2O4 +XCeO2 in purity and purity structure were prepared at multi–concentration X (0.0,0.05,0.10,0.15, and 0.20) using the solid state interaction method at a temperature (1000 °C) for four hours in air. The XR-diffraction shows that the prepared powder samples have a spinal structure at single cubic phase. The lattice parameters were decreasing from 8.331 to 8.3021 with increasing concentration of cerium’s Ionic Ce4+, also the crystal volume for purity samples is larger than in purity samples, decreasing from (578.217 to 571.993) A°3 with increasing concentration. However, the real and imaginary dielectric constants were measured for both pure and in purity samples by Ce4+. The dielectric constant shows that up to down decreases with increasing frequency. However, the x-ray density was increasing from 6.887 g/cm3 to 6.963 g/cm3 with increasing concentration. The conductivity of alternating current for preparing the sample increased firstly with frequency and remained constant, then a constant behavior was observed at higher frequencies. The microscopic pharmaology structure using the tunneling electron microscopy, that which particles have a spherical structure.